A Collaborative Approach to Iron Ore Beneficiation at Assmang Khumani Processing Plant - S Döpp (The Australasian Institute of Mining and Metallurgy, 2011)
Commencing with early experiences in iron ore beneficiation made at Beeshoek Mine, the paper follows through the process of extensive mineralogical and metallurgical investigations carried out during feasibility study. The paper will discuss the design process and logic followed over the last years, the challenges and decisions the design team faced in order to draw the conclusions that ultimately resulted in today’s value add approach at Assmang’s Khumani Operations.As integral part of the benefi ciation concept, a focus is set on the jigs, explaining the plant concepts, planned expansions and their contribution to the overall value add approach at the mine.The case study is intended to describe the outcomes of the design versus the actual achieved and the further value add projects to be implemented. As for future prospect, the incorporation of Wet High Intensity Magnetic Separation (WHIMS) demonstrates Assmang Khumani’s pursuit to maximise productivity and overall recovery.DMS was evaluated as an alternative to jigging within a comparative test work study, but in conclusion the option had to be excluded due to its inability to achieve the high density cut point required to achieve the sales specifi cations. In contrast, the investigation on producing an additional middlings fraction on the lumpy ore jigs prove to be an adequate option for further improvements of overall mass yield. With further liberation, a saleable product will be achieved by secondary beneficiation on Fines Jigs and WHIMS.Concluding, jigs are considered the most viable and cost effective benefi ciation process for off-grade ore +0.8 - 32 mm at Beeshoek as well as at Khumani, while WHIMS is the process under consideration for super fines recovery.